Analisis Persediaan Bahan Baku untuk Meningkatkan Kapasitas Produksi pada UD Yaman di Desa Lasara Kecamatan Namohalu Esiwa (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is based on a problem encountered at UD. Yaman, located in Lasara Village, Namohalu Esiwa District, North Nias Regency. Their operational activities as a supplier producing various types of furniture faced various obstacles in increasing production capacity due to difficulties in accurately predicting raw material inventory. This research used a quantitative method with a descriptive approach to increase production capacity through inventory forecasting. Field observations indicated that UD. Yaman's raw material procurement was carried out without a systematized approach, meaning that UD. Yaman's raw material procurement was based on demand without predicting demand for a specific period. Furthermore, the results of the exponential smoothing forecasting approach showed that, with an error rate of 0.1, the smallest forecast was 14, and the forecast yielded 548 for the August 2025 period, which was close to the highest actual sales figure of 575 m3. The results of this study recommend implementing a structured exponential smoothing method, specifically using an α value of 0.1, to increase production capacity at UD. Yaman, which can help increase profits.